A study of Malaysian secondary school student’s perspectives on the challenges faced in ESL reading comprehension - Mannudhini, Kumar (2023)

(untitled)
Reading comprehension refers to the ability to process the key points and the content of the specific texts. The government mandates it as a requirement for secondary school students to score well on their examinations. This study primarily focuses on secondary school students' perspectives on the difficulties they have with reading comprehension. Despite the fact that there are few studies on the subject, but students seem to have difficulties, which drives researchers to explore why they still have difficulties in modern society despite the fact that many resources are available to assist them. There are two objectives that guide this research which are to identify the difficulties experienced by Malaysian secondary school students when reading ESL reading comprehension texts and also to provide an in-depth overview of the strategies being used by Malaysian secondary school students to improve their ESL reading comprehension skill. Purposive sampling was used by the researcher to choose the respondents, who were form 4 students from Sekolah Menengah Kebangsaan Buntong in Ipoh. A semi structured interview was conducted to obtain the respondents' responses. Additionally, the data and findings were processed using thematic analysis, which produced specific themes. Findings shows that student’s perspectives on the difficulties faced in ESL reading comprehension can be categorised into four themes and three themes of strategies used by the secondary school students. Several recommendations have been made for future researchers who are interested in probing deeper into this field.